PENERAPAN DAN EVALUASI TATA KELOLA TEKNOLOGI INFORMASI DENGAN FRAMEWORK COBIT 5 DOMAIN MEA DI APOTEK ANANDA RANTEPAO - Madika, Garry Fatrick Bianca; Tambotoh, Johan (Program Studi Pendidikan Informatika, Universitas Citra Bangsa, 2024)
Information technology is one of the fields of science that can provide added value to a company so that the performance of the company can run effectively and efficiently. The role of it is very important to achieve the vision and mission of the company so that good governance is needed. Good IT governance will help all factors related to the use of it to make it easier to obtain profits as expected by the company. Therefore, the role of it is very important for the company to achieve its goals. IT management is a form of planning the use of it in accordance with the vision, mission and objectives of the company. Control and direction of it will minimize the risks that will occur so that the use of it can provide added value to the company to achieve its goals. Therefore, Ananda Rantepao pharmacy must get an application in the MEA Domain (monitor, evalute, and asses). COBIT (Control Objective for Information Technologies) is a collection of information and IT governance frameworks that represent structured and controllable activities. MEA (monitor, evaluate, and assess) is the domain of COBIT 5 that is used to conduct audits and IT Governance at Ananda Rantepao pharmacies. The use of COBIT 5 framework can be implemented on all types of organizations and companies of any size. The implementation of IT governance with the COBIT 5 domain MEA framework at Ananda Rantepao Pharmacy is expected to maximize the company's performance with the use of it in accordance with the objectives. Apotek Ananda Rantepao has not conducted an audit on existing IT so that the level of IT capabilities is not yet known, therefore it is necessary to conduct IT governance so that information technology can be controlled and work efficiently. The methods of this study are quantitative methods that use surveys or questionnaires that will be given to the subject of research to obtain conclusions, and qualitative methods obtained from interviews and observations on the company for accurate analysis results.